The legal and social aspect of transsexuality among Muslims: A study in Muslim countries with special reference to Iran / Zahra Sarcheshmehpour - Zahra , Sarcheshmehpour (2019)
This thesis aims to study the Islamic and jurisprudential perspectives of transsexuality in the contemporary age by scrutinizing the primary sources of Islamic law, analyzing the opinions of religious leaders and Muslim jurists from different Schools of thought such as Shiite and Sunni, as well as surviving different approaches of majority Muslim countries to this subject. Doctrinal methodology was used in this research and some interviews in the form of questionnaires as an empirical study were conducted to support it. The findings of this research revealed that gender identity disorder is considered as an inherent defect and abnormality by the Will of Allah, which implies that individuals with gender identity disorder are not sinners and any surgical treatment to rectify physical defects is not a sinful act. This study also found that, sex reassignment surgery is considered as the most medically effective treatments for gender identity disorders and increases satisfaction and the quality of transsexuals’ life after surgery in compare with before surgery. It was also found that despite the acknowledgement by the Quran and Sunnah of the existence of individuals with abnormal sexuality, Transsexuals (TS) are still subjected to numerous forms of abuse. They continuously face discrimination, arrest, torture and harassment, even in Islamic societies. It is hoped that these findings provide a congruent and supportive environment for transsexuals, where they as citizens can live fulfilling lives with maintaining their citizenship, gender and human rights.